2003
DOI: 10.1016/s0014-5793(03)00571-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential signaling through NFκB does not ameliorate skeletal myoblast apoptosis during differentiation

Abstract: During 23A2 skeletal myoblast di¡erentiation, roughly 30% of the population undergoes apoptosis. Further, constitutive signaling by G12V:H-Ras or Raf:CAAX abrogates this apoptosis. In this study, we demonstrate an increase in NFU UB activity in myoblasts that have survived and are expressing muscle-speci¢c genes. NFU UB activity is also elevated in myoblasts expressing constitutively active G12V:H-Ras but not Raf:CAAX. Expression of a dominant negative IU UB (IU UB-SR) su⁄cient to eliminate this elevated level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
(91 reference statements)
1
12
0
Order By: Relevance
“…These data suggested that the ability of S100B to protect myoblasts against apoptosis and to stimulate myoblast proliferation relied on a single pathway, the Ras-MEK-ERK1/2 pathway that converged onto two different downstream targets that is NF-kB and Rb, respectively. In this regard, it was shown that proliferation arrest and apoptosis in myoblasts cultivated in DM are two separate events (Dee et al, 2003). Remarkably, the ability of S100B to induce cyclin D1 expression was manifest at as low as 10 pM (Fig.…”
Section: S100b Stimulates Myoblast Proliferation Via Ras-mek-erk1/2 Amentioning
confidence: 88%
“…These data suggested that the ability of S100B to protect myoblasts against apoptosis and to stimulate myoblast proliferation relied on a single pathway, the Ras-MEK-ERK1/2 pathway that converged onto two different downstream targets that is NF-kB and Rb, respectively. In this regard, it was shown that proliferation arrest and apoptosis in myoblasts cultivated in DM are two separate events (Dee et al, 2003). Remarkably, the ability of S100B to induce cyclin D1 expression was manifest at as low as 10 pM (Fig.…”
Section: S100b Stimulates Myoblast Proliferation Via Ras-mek-erk1/2 Amentioning
confidence: 88%
“…Differentiation was induced and monitored after switching cells from growth medium to differentiation medium (DM), which consists of BME, 1% P/S and 0% FBS [4,[20][21][22][23][28][29][30][31]. Cells were incubated at 37°C in 5% CO 2 .…”
Section: Cells and Cell Culturementioning
confidence: 99%
“…Despite the wealth of molecular knowledge detailing skeletal myoblast determination and differentiation, information regarding the molecular mechanisms controlling the apoptosis associated with skeletal myoblast differentiation is limited [3,4,[17][18][19][20][21][22][23][24]. The molecular mechanisms responsible for apoptosis in other systems, however, have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3-kinase/Akt pathway, the Raf/MEK/MAPK pathway, and the NFkB pathway remain the best characterized downstream targets of activated Ras (Finco et al, 1997;Ramirez De Molina et al, 2004;White et al, 1995). We have previously reported that both signaling through MEK and NFkB (Dee et al, 2003) are constitutively active in 23A2 myoblasts expressing G12V:H-Ras. Herein, we report that signaling through PI3-kinase is constitutive in myoblasts expressing either G12V:H-Ras.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that inhibiting either MEK/MAPK or NFkB (Dee et al, 2003) does not revert the G12V:H-Ras-induced effect on differentiation and the associated apoptosis. Furthermore, simultaneous inhibition of PI3-kinase, rapamycin, MEK and NFkB and does not restore the ability of G12V:H-Ras-expressing myoblasts to differentiate or undergo the associated apoptosis ( Fig.…”
Section: Constitutive Pi3-kinase Signaling Is Not Required For the Acmentioning
confidence: 99%